Slavery and the Domestic Slave Trade in the United States by the Committee Appointed by the Late Yearly Meeting of Friends Held in Philadelphia in 1839 - (:unkn) unknown (Merrihew and Thompson, 1841)
Slavery and the Domestic Slave Trade in the United States by the Committee Appointed by the Late Yearly Meeting of Friends Held in Philadelphia in 1839. Includes excerpts from Joseph John Gurney’s Familiar letters to Henry Clay of Kentucky, describing a winter in the West Indies (Cf. p. 36).
MS/146 Slavery Papers, Speeches & Manuscripts. Original page size: 4.5" x 7.75", Fragile condition. Binding string broken. 45 pages. UUID: 395d8971-614a-43e0-8154-346b856d4932 Scanned from original print. Processed by Dallas Suttles (dasuttles@valdosta.edu) at Valdosta State University Archives and Special Collections, 6/23/2016. 600 DPI. OCR Abbyy FineReader 11.0. Cropped to 4.0" x 7.00". Access (B/W. 43 pages).
Keywords: Slavery--United States; Slavery and the Church -- United States -- History